19F NMR studies on ionic conduction pathways in tysonite-CeF3. (February 2022) - Murakami, Miwa; Mineshige, Atsushi
Abstract: There has been a long-standing controversy over ion conducting pathways in tysonite. To unravel the pathways in CeF3, high-resolution MAS NMR spectra of 19 F in CeF3 at −40–240 °C are analyzed on the bases of the calculated dipolar coupling tensor between 19 F and paramagnetic electron spins at Ce 3+ to assign the three spinning-sideband manifolds for the three crystallographically inequivalent sites (F1, F2, and F3). Clearly resolved sideband manifolds for F1∼F3 at 240 °C indicate that ion exchange among the three sites is not fast enough to affect the 19 F spectrum, whereas F1 motion is suggested by its broader linewidth. Further, we show that addition of only 0.1% Sr 2+ in CeF3 (Ce1- x Sr x F3- x ( x = 0.001)) brings significant effects on F-ion mobility. While some of the F2 ions remain at the F2 site, most of the F3 ions undergo exchange motion between F1 at 240 °C. The preference of the exchange pathways in CeF3 is thus consistent with that postulated for LaF3, that is, F1–F1 exchange occurs first followed by F1–F3, and F1–F2 exchange is most restricted. Graphical abstract: Image 1 Highlights: 19 F MAS NMR spinning sideband manifolds of CeF3 are assigned to F1∼F3. The dipolar interaction between 19 F and electrons of CeF3 are considered explicitly. In CeF3, F1–F1 exchange occurs first followed by F1–F3 and F1–F2 is most restricted. Only 0.1% of Sr 2+ doping in CeF3 does enhance F mobility appreciably.